Evaluation of a Sexual Transmitted Infection Prevention Program Among University Students in Beira City Central Mozambique: A Study Protocol - Zango, Arlinda Basílio; Crutzen, Rik; de Vries, Nanne (Frontiers in Reproductive Health, 2021)
Background: Unhealthy sexual behaviors, such as unprotected sexual intercourse and lack of using screening services increase cyclical transmission of sexually transmitted infections including Human Immunodeficiency Virus (HIV), especially among young adults. Hence health promotion programs can contribute to reduce the consequences, by changing (determinants of) these behaviors. Such interventions need to embrace a comprehensive approach and apply theory-and evidence-based methods. This article describes the protocol for a process and effect evaluation study of a sexually transmitted infection prevention program among university students in Beira city, central Mozambique. Methods: The on-going program at Universidade Católica de Moçambique is described following the six steps of Intervention Mapping (IM), with a focus on the evaluation plan (i.e., the final step in IM). The details regarding previous steps in the protocol are briefly described as well, as they lay the foundation for the final step. The process evaluation will apply qualitative and quantitative methods to gain insight in the context, reach, dose delivered, dose received and recruitment. Interviews with closed and open-ended questions will be conducted with program implementers and users. A quasi-experimental non-equivalent control group design is used to evaluate the effectiveness. A cohort of university students will be followed for six months. Self-administrated questionnaires will be used to collect data every three months. Discussion: A combination of process and effect evaluation is proposed. This is a useful and fruitful procedure, since concurrent process evaluation can allow researchers to better interpret findings from the effect evaluation and understand how the intervention might replicate in similar contexts. We decided to follow the IM approach since, it is a theory-and evidence-based, systematic and detailed guide regarding what to do at every steps. A quasi-experimental non-equivalent control group design was chosen to fit the context of the study and generate outcomes with high external validity.